The Law of Dropshiping Buying According to Madzhab Malikiyah and Syafi'iyah - Handoko, Prio; Ibrahim, Duski; Bukhari, KA (Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to examine the sale and purchase of dropshipping which fall into the category of Salam, Ijarah and Wakalah contracts and laws according to the Malikiyah and Syafi'iyah schools of thought. The research method used is qualitative with primary data sources obtained by interviewing the sources, with secondary data in the form of literature studies of previous research and fiqh books of the Malikiyah and Syafi'iyah schools. The results of the study show that the dropshipping buying and selling system is included in Salam, Ijarah and Wakalah contracts, as Syafi'iyah's opinion allows salam contracts which have a short estimated delivery time, called salam haal and with cash advance payments when the transaction takes place. As for the Maliki school, it does not allow the salam haal contract because the estimated time for delivery of the goods is short.